The phenomenon of near death experience (NDE): Its critical implications on Nietzsche's existential philosophy - Gojocco, Victor Elazaegui (Animo Repository, 2018)
Nietzsche as a leading figure of atheistic philosophy have greatly influenced 19th century European philosophy with his famous resounding categorical statement God is dead. The philosophy have settled most of the philosophical debates on issues of the possibility of the soul, of any transcendent reality and of the possibility of a divine being. His philosophy greatly contributed to establishing the very foundations for the philosophy of existentialism with its principles resting on earthly values. Both Nietzsche and existentialism claims life's absurdity, meaninglessness and devoid of purpose and with it, the absence of an afterlife. His philosophy has great explanatory power and coherence offering the human individual to affirm life amidst all its harsh realities. Refutations in existential philosophy especially in Nietzsche's philosophy has centered mainly on certain logical inconsistencies wherein essentially are all theoretical and speculative in nature With the recent emergence from the medical field, the phenomenon called Near Death Experiences (NDE) there had been revealing testimonies from experiencers of their fantastic claims of experiencing something more, right after they have been pronounced dead. To date more than 15 million people recorded of having claimed if not exactly the same, similar accounts of near death experiences. What is mind-boggling is that these claims clearly appear to clash with the many philosophical claims found in Nietzsche's philosophy. What is most significant is that majority if not all have claimed the same experience of not ending up in nothing after they have died. Majority of the claims appear to declare complete opposition to many of Nietzsche's philosophical principles. That primarily, earthly life has purpose, meaning, that there is an afterlife, a soul, and most of all an affirmation of Gods (the Divine) existence. Thus with the presence of NDE phenomenon there would have to be a call for a necessary revisions and fundamental overhaul of the many current perspectives in Nietzsches philosophy together with Existentialism. Thus the objective of this research is to present and examine how the implications of the phenomena of near death experience establish viable perspectives and arguments against the major concepts of Nietzsche's philosophy adopting two modern method of philosophical inquiry called experimental philosophy (X-Phil) and Interpretative Phenomenological Analysis (IPA). X-Phil allows the use of empirical findings from the phenomena being examined. IPA allows a more phenomenological approach in studying the phenomena based on the experiencers lived experience. With the two frameworks, X-Phil and IPA, the study will show how the core elements of the near death phenomena together with the 9 line of evidence would greatly affect the major concepts found in Nietzsche's philosophy. What is found in the near death experience appear to directly oppose many of Nietzsche's major concepts.